Synergistic Effects of Organic and Chemical Fertilizers on Microbial-Mediated Carbon Stabilization: Insights from Metagenomics and Spectroscopy - Wei Wang; Yue Jiang; Shanshan Cai; Yumei Li; Juanjuan Qu; Lei Sun (Agronomy, 2025)
Fertilization management constitutes a critical determinant of agroecosystem productivity. Reasonable fertilization can increase the organic matter content in soil; however, the potential mechanism of how different fertilization regimes impact soil carbon sequestration is unclear. We hypothesized that the combined application of biochar and organic fertilizer would enhance soil carbon sequestration by improving soil physicochemical conditions, increasing microbial activity, and promoting the accumulation of stable forms of carbon. This study systematically investigated different regimes, including the application of chemical fertilizer alone (SCN), chemical fertilizer with biochar (SCB), chemical fertilizer with organic fertilizer (SCO), and chemical fertilizer with both biochar and organic fertilizer (SCBO), on soil physiochemical properties, enzyme activities, labile organic carbon fractions, microbial carbon fixation gene expression, and community composition. The results demonstrated that (1) the application of organic materials significantly enhanced soil nutrient levels and enzyme activities, with the best performance from SCBO; (2) the organic materials increased the labile soil organic carbon (SOC) content and the carbon pool management index, with SCO showing the highest at 69.82%; (3) SCB and SCBO improved the stability of soil carbon components by increasing the proportion of Aromatic C; and (4) the carbon fixation genes ACAT and sdhA exhibited the highest abundance in SCBO. In parallel, the relative abundance of Actinomycetota increased with the application of organic materials, reaching its peak in SCBO. Mantel testing revealed a strong correlation between microbial community composition and SOC, emphasizing the importance of SOC in microbial growth and metabolism. Moreover, the strong correlation between carbon fixation genes and aromatic carbon suggested that specific carbon forms, particularly aromatic structures, played a critical role in driving microbial carbon fixation processes.